Prevalence of congenital heart disease in patients undergoing surgery for major gastrointestinal malformations: an Indian study. Issue 1 (5th June 2015) - Gokhroo, Rajendra K; Gupta, Sajal; Arora, Garima; Bisht, Devendra S; Padmanabhan, Deepak; Soni, Varsha
Abstract : Background: The association of congenital heart disease (CHD) with malformations of the gastrointestinal (GI) tract/abdominal wall is known. The rates of cardiac malformations reported in previous studies of these anomalies are highly variable. Objective: To find the prevalence and pattern of CHD in patients with major gastrointestinal malformations (anorectal malformations, oesophageal atresia/tracheo-oesophageal fistula, and omphalocoele) undergoing surgery at a tertiary care hospital in India. Methods: From July 2012 to December 2013, 43 patients (34 (79%) male, 9 (21%) female) were evaluated by clinical examination, ECG, chest radiography, and colour Doppler echocardiography. Results: Of the 43 patients, 26 (60.46%) had CHD. The most common GI malformation was anorectal malformation: 32 cases (74.41%), of whom 16 (50%) had CHD. The second most common malformation was oesophageal atresia/tracheo-oesophageal fistula: 5 cases (11.62%), all (100%) with CHD. The third group comprised patients with omphalocoele: 4 cases (9.3%), 3 of whom (75%) had CHD. The fourth group comprised patients with VACTERAL (vertebral anomalies, anal atresia, cardiovascular malformations, tracheo-oesophageal fistula, renal and limb anomalies) association—2 cases (4.6%), all (100%) with CHD. The most common CHD was isolated atrial septal defect (ASD) (73%), followed by ASD + ventricular septal defect (VSD) + patent ductus arteriosus (PDA) (7.6%), ASD + VSD (3.8%), ASD + PDA (3.8%), VSD (3.8%), PDA (3.8%), and coarctation of the aorta (3.8%). Conclusions: We found the frequency of CHD in patients with GI malformations was very high, the most common presentation being ASD. Our study indicates the need for larger scale studies to determine the prevalence of CHD in patients with GI malformations in the Indian population.